Cloning and expression of ga protein of nip ah virus in yeast expression system - Chang Ching, Ching (Universiti Sains Malaysia, 2008)
Nipah virus (NiV) is a deadly zoonotic paramyxovirus that has emerged and reemerged over the last 10 years. In human, the infection leads to encephalitis with 92% mortality rate. This has underlined the importance for the development of a vaccine candidate in preventing such zoonotic disease. In previous study, the gene encoding the NiV glycoprotein (NiV -G) was cloned into the yeast Pichia Pastoris expression vector (pZMF) under the control of AOXI promoter. However, the recombinant G glycoprotein expression was found to be highly unstable in this system. Therefore, the stability of the recombinant protein was investigated by studying one of the truncated gene fragment (GA gene). The truncated gene encoding the gene sequence 1-867 was cloned and expressed in the same biological system. The detection of the truncated recombinant protein was performed through Western blot analysis. The result of this study indicated that the truncated fragment was stable and the expression was consistent with protein molecular weight of 40 kDa. The absent of degradation incident in this study had suggested that GA gene fragment was stable in full length G-glycoprotein expression. In addition, the truncated recombinant protein could be utilized as a promising vaccine candidate if the recombinant protein was found to be highly antigenic and immunogenic.